2020
DOI: 10.3390/nu12061786
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs6564851 in the BCO1 Gene Is Associated with Varying Provitamin a Plasma Concentrations but Not with Retinol Concentrations among Adolescents from Rural Ghana

Abstract: In sub-Saharan Africa, vitamin A deficiency constitutes a severe health problem despite various supplementation and food fortification programs. Given that the intake of preformed vitamin A from animal products remains low in these countries, an efficient metabolization of plant-based provitamin A carotenoids is essential. Previously, adolescents in rural Ghana have shown high total plasma carotenoid concentrations, while 36% had a vitamin A deficiency (defined as plasma retinol < 0.7 µmol/L). Hence, the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…An example of nutrition marker we classify as possible is BCO1 (rs6564851). According to our research ( Table 4 ), there are 4 studies with a number of total subjects analyzed of 328 (Yabuta et al, 2016 ; Moran et al, 2019 ; Amengual et al, 2020 ; Graßmann et al, 2020 ). Our judgement of the underlying knowledge of the biological mechanism involved is medium and there are some cases where a potential intervention may not have the desired effect.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…An example of nutrition marker we classify as possible is BCO1 (rs6564851). According to our research ( Table 4 ), there are 4 studies with a number of total subjects analyzed of 328 (Yabuta et al, 2016 ; Moran et al, 2019 ; Amengual et al, 2020 ; Graßmann et al, 2020 ). Our judgement of the underlying knowledge of the biological mechanism involved is medium and there are some cases where a potential intervention may not have the desired effect.…”
Section: Resultsmentioning
confidence: 95%
“…Each additional copy of the rs9939609 A allele has been associated with a BMI increase of a mean of 0.10 Z -score units, equivalent to ~0.4 kg/m 2 (Sonestedt et al, 2009 ; Tanofsky-Kraff et al, 2009 ; Zhao et al, 2014b ). For the observed genotypes in APOA2 and FADS1 , there is no associated effect (Yabuta et al, 2016 ; Huang et al, 2017 ; Ching et al, 2019 ; Moran et al, 2019 ; Amengual et al, 2020 ; Graßmann et al, 2020 ; Wang et al, 2020 ). For LEPR , a study found that rs1137101 AG and GG carriers with a high fat total intake had 3.0 times higher risk of obesity and 4.1 times higher risk of high cholesterol levels than those with a low intake of total fat (Domínguez-Reyes et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The associations between other common variants of the gene and genes adjacent to the BCO1 gene and serum β-carotene status also have been extensively reported ( 40 45 ). The rs6564851 common variant located about 8 kb upstream of the BCO1 gene is reported to be associated with circulating levels of β-carotene in different ethnic groups ( 40 , 43 , 44 ). The rs6564851 variant is located within a haplotype that includes other genetic polymorphisms ( Figure 1A ).…”
Section: Intestinal Absorption Of β-Carotenementioning
confidence: 99%